Encapsulated n-Butylidenephthalide Efficiently Crosses the Blood–Brain Barrier and Suppresses Growth of Glioblastoma - Lin YL; Huang XF; Chang KF; Liao KW; Tsai NM (International Journal of Nanomedicine, 2020)
Yu-Ling Lin, 1,* Xiao-Fan Huang, 2, 3,* Kai-Fu Chang, 2, 3,* Kuang-Wen Liao, 4–6 Nu-Man Tsai 2, 7 1Agricultural Biotechnology Research Center, Academia Sinica, Taipei 11529, Taiwan, Republic of China; 2Department of Medical Laboratory and Biotechnology, Chung Shan Medical University, Taichung 40201, Taiwan, Republic of China; 3Institute of Medicine of Chung Shun Medical University, Taichung 40201, Taiwan, Republic of China; 4Department of Biological Science and Technology, National Chiao Tung University, Hsinchu 30010, Taiwan, Republic of China; 5Institute of Molecular Medicine and Bioengineering, National Chiao Tung University, Hsinchu 30010, Taiwan, Republic of China; 6Graduate Institute of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung 80708, Taiwan, Republic of China; 7Clinical Laboratory, Chung Shan Medical University Hospital, Taichung 40201, Taiwan, Republic of China*These authors contributed equally to this workCorrespondence: Nu-Man TsaiDepartment of Medical Laboratory and Biotechnology, Chung Shan Medical University, No. 110, Sec. 1, Jianguo N. Road, Taichung 40201, TaiwanTel +886-4-24730022 ext. 12411Fax +886-4-23248171Email numan@csmu.edu.twBackground: n-Butylidenephthalide (BP) has anti-tumor effects on glioblastoma. However, the limitation of BP for clinical application is its unstable structure. A polycationic liposomal polyethylenimine (PEI) and polyethylene glycol (PEG) complex (LPPC) has been developed to encapsulate BP for drug structure protection. The purpose of this study was to investigate the anti-cancer effects of the BP/LPPC complex on glioblastoma in vitro and in vivo.Methods: DBTRG-05MG tumor bearing xenograft mice were treated with BP and BP/LPPC and then their tumor sizes, survival, drug biodistribution were measured. RG2 tumor bearing F344 rats also treated with BP and BP/LPPC and then their tumor sizes by magnetic resonance imaging for evaluation blood–brain barrier (BBB) across and drug therapeutic effects. After treated with BP/LPPC in vitro, cell uptake, cell cycle and apoptotic regulators were analyzed for evaluation the therapeutic mechanism.Results: In athymic mice, BP/LPPC could efficiently suppress tumor growth and prolong survival. In F334 rats, BP/LPPC crossed the BBB and led to tumor shrinkage. BP/LPPC promoted cell cycle arrest at the G 0/G 1 phase and triggered the extrinsic and intrinsic cell apoptosis pathways resulting cell death. BP/LPPC also efficiently suppressed VEGF, VEGFR1, VEGFR2, MMP2 and MMP9 expression.Conclusion: BP/LPPC was rapidly and efficiently transported to the tumor area across the BBB and induced cell apoptosis, anti-angiogenetic and anti-metastatic effects in vitro and in vivo.Keywords: glioblastoma, n-butylidenephthalide, blood–brain barrier, drug delivery